Dynamic modeling and optimization of an industrial fluid catalytic cracker. (July 2015) - Sildir, Hasan; Arkun, Yaman; Canan, Ummuhan; Celebi, Serdar; Karani, Utku; Er, Ilay
Graphical abstract: Highlights: An industrial fluid catalytic cracking plant is modeled. The riser and the regenerator units are modeled using first principles. For the fractionator an empirical model is developed by using temperature cut points. Model parameters are estimated from actual plant data. Economic optimization and dynamic simulations show the potential use of the model for real-time optimization and control. Abstract: Fluid Catalytic Cracking (FCC) is an important process which is used to convert heavy petroleum fractions into more valuable lighter products. In this work, the FCC process consists of the reactor, the regenerator and the fractionation units. Modeling is challenging due to the complex reaction chemistry and the interactions among the different process units. The reaction medium is modeled by the method of discrete lumping that uses narrow fractions. As a result, the number of discrete lumps (or pseudo-components) to model the process increases and this enables better prediction of fractionation products. For the reactor, we present a new kinetic model that includes a yield function for the cracking products. Kinetic constants and heat of cracking are correlated with the average boiling point of the pseudo-components. These correlations are next used in the development of first-principles models for the riser and the regenerator units. In addition, an empirical model is constructed for the purpose of predicting the individual amounts of the fractionation products from the reactor's effluent. Using parameter estimation, model parameters are estimated from actual industrial data. Model predictions match the plant measurements closely. Simulation and optimization results show that the developed model offers significant potential for use in real-time optimization and control.